Kajian Literatur: Peran Sifat Fisika-Kimia Obat Dalam Efektivitas Sistem Penghantaran Transdermal Patch - Lu’lu Jannah QA; Nazhara Dwi Lestari; Sri Wahyuni; Naela Izzatun Nissa; Fahmi Hasby Assidiqy; Jaira Jacquitta Putri; Rifa Husnul Khotimah; Dwintha Lestari (Universitas Nurul Jadid, 2025)
Limited drug permeation across the stratum corneum remains a major challenge in transdermal patch development, while integrated analyses linking physicochemical drug properties with formulation design are still scarce. This study aimed to synthesize the influence of physicochemical parameters on the effectiveness of transdermal patch systems through a descriptive analytical literature review of seven peer-reviewed articles published within the last decade. The analysis demonstrates that drugs with low molecular weight (<500 Da), optimal lipophilicity (log P 1–3), low melting point (<200°C), pKa compatible with skin pH, low polar surface area, and limited hydrogen bonding capacity exhibit considered superior transdermal permeability. Furthermore, interactions between drugs and formulation components including polymer matrices, plasticizers, and penetration enhancers were found to modulate skin permeation mechanisms and drug release profiles. This review highlights that the success of transdermal patches relies on the synergistic optimization of physicochemical drug properties and mechanism-based formulation strategies, providing a rational framework for the development of effective and clinically relevant transdermal delivery systems